Vulnerability assessment due to wind storm impact - Mohamad Hafizi, Baharom (2014)
Wind related damage is increasing in Malaysia. The information related to wind characteristics is very important. High wind speed area will result higher rate of damage. In this study, the wind speed identities are finding out by using Geographical Information System (GIS) application and the locations are located. Mean wind speed from weather station are been use. Spatial analyses are conducted to Peninsular Malaysia. From the analysis it shows that wind related disasters are tendency to follow any high wind speed. Therefore it can conclude that the higher wind speed will cause high rate of wind damage.